Systemic conditions of diabetic patients diagnosed with apical periodontitis - SILVA,Poliana Amanda Oliveira (2021)
ABSTRACT Objective: This study aimed to evaluate the association between glycemic control status in type 2 diabetes mellitus (T2DM) patients and apical periodontitis. Methods: Twenty-seven patients were involved in this study. The survey was based on anamnesis, intra and extra oral examination and radiographic evaluation. Diabetes mellitus information involved type of diabetes and blood glucose analysis. Patients were divided according to their metabolic control status (glycemic controlled and poorly controlled T2DM patients). Results: A higher fasting blood glucose level (p = 0.004) and a higher percentage of HbA1c (p = 0.0001) were demonstrated in poorly controlled T2DM patients when compared to glycemic controlled T2DM. However, the frequency of apical periodontitis and the elapsed time since diabetes mellitus diagnosis were higher in controlled T2DM patients, reaching 64%. Nevertheless, controlled T2DM patients presented a higher number of apical periodontitis cases (p < 0.05). Findings support that controlled patients T2DM presented higher presence of apical periodontitis than poorly controlled T2DM ones. In these patients, the time elapsed since the diagnosis was higher, which may have provided a longer period of oscillation and/or uncontrolled metabolism. Conclusions: Therefore, it might contribute to the development and maintenance of apical periodontitis in glycemic controlled patients of this study.